A BOOK REVIEW: FEMINISM ANDNERSUS FEMINITY OF MODERN WOMEN - B. Retang Wohangara (Celt: A Journal of Culture, English Language Teaching & Literature, 2007)
One important theme attached to pop culture is the politics of representation and sub-cultural identity. The pop singer Madonna and then the Spice Girls are frequently regarded as the representation of modern women offering a different face of feminism ideology. Successfully entering the market competition, Madonna, through her cry of 'material girl', characterizes herself as an independent woman in the still dominating patriarchal world while challenging the burden of morality placed on the shoulders of women. She asks young women to rebel against male-centred traditions and unashamedly exposes her sensuality as a source of power and even domination, or in short celebrating 'being women'. The flag of Girl Power is also waved by the 1990'sBritish female singers, the Spice Girls, who call young girls to "be strong, be brave, be loud and control your own destiny. Believe that your self can do anything you want to do and be confident. We have to be independent, but it does not mean that you don't need a boy" (Swastika 2004: 66).